Review Performa Mesin pada Sepeda Motor Dengan Penyesuain Waktu Pengapian terhadap Penggunaan Bahan Bakar Pertamax Green 95 - Andy Rianata; Dan Mugsidi (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2025)
The development of the number of motorized vehicles is very high at this time. The phenomenon in 2025, almost all motorcyclists have problems with fuel that does not match the RON. This study aims to analyze engine performance on motorcycles by adjusting the ignition timing to the use of Pertamax Green fuel. This study is to analyze the use of fuel with octane 95 and ignition timing on engine performance on motorcycles. This research method uses a full open throttle valve in testing engine performance with a dyno engine, the fuel used is Pertamax Green with RON 95, and ignition that varies from 2.5° before top dead center from standard time, 5° before top dead center from standard time, 7.5° before top dead center from standard time, 10° before top dead center from standard time. The results obtained when using Pertamax Green fuel and changing the ignition, can change and increase engine performance and increase fuel efficiency, for perfect ignition is at 2.5° before the top dead center of the standard time. The torque obtained when using Octane 95: 15.30 N.m, an increase of 1.83 N.m from the standard timing. The power generated from Octane 95: 8.8 HP, an increase of 0.9 HP from the standard timing. And the lowest consumption produced by using Octane95:0.1340ml/s